2021
DOI: 10.3389/fpls.2021.667314
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination in Plant Meiosis: Recent Advances and High Throughput Methods

Abstract: Meiosis is a specialized cell division which is essential to sexual reproduction. The success of this highly ordered process involves the timely activation, interaction, movement, and removal of many proteins. Ubiquitination is an extraordinarily diverse post-translational modification with a regulatory role in almost all cellular processes. During meiosis, ubiquitin localizes to chromatin and the expression of genes related to ubiquitination appears to be enhanced. This may be due to extensive protein turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 204 publications
(301 reference statements)
0
5
0
Order By: Relevance
“…Ubiquitination of HvASY1 by HvST1 but not Hvst1 in vitro provides an indication that the lack of ZYP1 polymerization observed in Hvst1 may result from the loss of this post translational modification of ASY1, and potentially from other SC proteins. The ubiquitination cascade has a well-established and extensive role in meiotic progression across Eukaryota (45), and ubiquitin has been shown to localize to the chromosomal axes during meiotic prophase (47)(48). Osman, et al (49) previously identified proteasomal and ubiquitination related proteins in association with ASY1 in a pulldown from Brassica oleracea.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination of HvASY1 by HvST1 but not Hvst1 in vitro provides an indication that the lack of ZYP1 polymerization observed in Hvst1 may result from the loss of this post translational modification of ASY1, and potentially from other SC proteins. The ubiquitination cascade has a well-established and extensive role in meiotic progression across Eukaryota (45), and ubiquitin has been shown to localize to the chromosomal axes during meiotic prophase (47)(48). Osman, et al (49) previously identified proteasomal and ubiquitination related proteins in association with ASY1 in a pulldown from Brassica oleracea.…”
Section: Discussionmentioning
confidence: 99%
“…The IAPs can block caspase activation via two main mechanisms: they can act as enzyme blockers, blocking substrate entry into the caspase active domain, or target the caspases for proteasomal degradation via the process of ubiquitination [26]. Ubiquitination is an evolutionarily conserved process to promote the degradation of proteins tagged with the ubiquitin peptide [28]. In both mechanisms, the end result is a functional decrease in caspase activity and, thus, a greater degree of apoptosis inhibition.…”
Section: Apoptosis Pathways In Health and Diseasementioning
confidence: 99%
“…Late Pachytene stage). However, by which mechanism HEI10 can coarsen and how it is related to other ubiquitination processes during meiosis require further investigations (Orr et al, 2021;Ren et al, 2021). It is worth underlining that the analysis of pachytene bivalents using electron microscopy had already noticed different sizes and shapes of early (poorly interfering) versus late interfering 'recombination nodules' (RN) localize along the synaptonemal complex (Anderson and Stack, 2005).…”
Section: A Model Of Co Interference Based On Hei10 Coarsening Along T...mentioning
confidence: 99%